ANIMATION MOVIES FOR ENHANCING VOCABULARY: A QUANTITATIVE STUDY AMONG VOCATIONAL SCHOOL STUDENTS - Syaefani Arif Romadhon; Iin Indrayanti; M Taufik Qurohman (Journal of English Language Learning, 2022)
The purpose of this study was to analyse the effectiveness of using animated films to improve students' English learning, especially in vocabulary. Three vocabulary component points assessed are picture identification, word meaning and spelling. Before getting treatment in the form of watching English animated films, students did 30 pre-test questions. After watching the film students were also asked to work on post-test questions with the same number and types of questions. In this study, the design used was the One-Group Pre-test Post-test Design method. This research was conducted at SMK Karya Bhakti Brebes, there were 23 subjects. From the results of the T-Test Picture Identification, we can see that the results of the t count (tcount)> ttable or 3,766> 1,713. This shows that the initial hypothesis is accepted or it can be said that the use of the animated film method is effective to increase students' vocabulary, especially in picture identification. For the results of the T-test Word Meaning, namely t count (tcount)> ttable or 2,760 > 1,713 so it can be concluded that animated films are effective for increasing students' vocabulary. And for the results of the T-Test Spelling the value of t count (tcount) < ttable or 0.568 < 1.713, indicates that the learning method using animated films is less effective.